Hubungan Dukungan Keluarga dengan Tingkat Kepatuhan Melakukan Kontrol Rutin pada Penderita Diabetes Mellitus di RSU. Imelda Pekerja Indonesia - Nataria Yanti Silaban; Paskah Rina Situmorang; Edisyah Putra Ritonga; Ratna Dewi (Yayasan Literasi Sains Indonesia, 2022)
Diabetes Mellitus (DM) is a chronic condition where there is an increase in glucose levels in the blood because the body cannot produce or produce insulin or the body cannot use insulin effectively. In improving the compliance of DM sufferers, it is very important to find out several factors that cause non-compliance in DM sufferers. This type of research is quantitative using a cross-sectional approach to see the relationship between family support and compliance with carrying out routine control in diabetes mellitus sufferers at RSU Imelda Workers Indonesia with a sample size of 37 respondents. From the results of the analysis using the SPSS Chi-Square test system, it shows that there is a positive and significant relationship between family support and compliance with routine control at the RSU. IPI Medan with a p-value = 0.017, so it can be concluded that Ha accepts that there is a significant relationship between family support and compliance with routine control in diabetes mellitus patients. The conclusion is that there is a relationship between family support and compliance with routine control in diabetes mellitus sufferers.